ANALISIS KONFLIK LALU LINTAS SIMPANG TAK BERSINYAL (STUDI KASUS: SIMPANG 3 PARAK GADANG, KOTA PADANG) - Nemers, Excel; Boy, Wendi (Program Studi Teknik Sipil, 2024)
Traffic conflict is a situation where there is potential for accidents or collisions between vehicles, pedestrians, or other road users. An intersection is a location on the road where flows from different directions meet, often leading to traffic conflicts. This research aims to identify conflict points occurring at the Parak Gadang 3-way intersection, analyze the causes of traffic conflicts at that location, and formulate handling strategies to reduce or avoid traffic conflicts at the Parak Gadang 3-way intersection. The study utilizes the Traffic Conflict Technique (TCT) method. The results show there were 239 conflict events, categorized into 3 types: crossing (73.22%), merging (22.17%), and diverging (4.6%). Out of the total 239 conflicts, 17 were classified as serious conflicts, while 222 were non-serious conflicts. Based on time to accident analysis, this intersection is categorized as having non-serious conflicts. Keywords: Unsignalized intersection, Traffic conflict, Accident, TCT.